The effect of exotic grass Urochloa decumbens (Stapf) R.D.Webster (Poaceae) in the reduction of species richness and change of floristic composition of natural regeneration in the Floresta Nacional de Carajás, Brazil - FERREIRA,LEANDRO V. (2016)
ABSTRACT The introduction of exotic species is considered as one of the major causes of biodiversity loss. The National Forest of Carajás is one of the largest mineral provinces in the world. Mining activities caused changes of the natural habitats, leaving degraded areas after the mineral exploitation. One of the mining areas within FLONA Carajás was used for the extraction of gold. In the process of exploitation, a huge depression was formed by the removal of soil which was mounded up nearby. To prevent soil erosion of these mounds, an exotic grass, Urochloa decumbens (Stapf) R.D.Webster (Poaceae) was planted. The objective of this study was to compare the impact of this non-native grass on species richness and species composition of the natural regeneration in the degraded areas. Four areas were compared, two with and two without presence of U. decumbens. In each area, twenty four 1m²/plots were established. Species richness of the regeneration areas and population sizes were significantly lower in the plots where the exotic grass was present. Our study shows that U. decumbens had a negative effect on species richness and population density, and its presence changed the species composition and distribution of life forms of the natural regeneration.